1965
DOI: 10.3382/ps.0440015
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dietary Alterations, Hormones, and Blood Pressure on the Incidence of Dissecting Aneurysms in the Turkey

Abstract: fat by chicks. J. Agr. Sci. 40: 39^3. Duncan, D. B., 195S. Multiple range and multiple F tests. Biometrics, 11: 1-42. Essary, E. 0., 1961. The influence of added fat and protein in broiler rations on growth rate, dressing percentage, and other carcass characteristics. Thesis, unpublished. Michigan State University. Essary, E. O., L. E. Dawson, E. L. Wisman and C. E. Holmes, 1965. Influence of different levels of fat and protein in broiler rations on live weight, dressing percentage and specific gravity of carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

1967
1967
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
2
17
0
1
Order By: Relevance
“…DES depressed blood pressure, in confirmation of previous findings of Krista et al (1965) and Simpson and Harms (1965). Other treatments had no effect on blood pressure.…”
Section: Mortalitysupporting
confidence: 91%
See 2 more Smart Citations
“…DES depressed blood pressure, in confirmation of previous findings of Krista et al (1965) and Simpson and Harms (1965). Other treatments had no effect on blood pressure.…”
Section: Mortalitysupporting
confidence: 91%
“…High energy rations have been implicated as a contributing factor. The advent of these diets and the presence of atherosclerotic plaques at the rupture sites (Carnaghan, 1955;Gibson and de Gruchy, 1955) raise the question of the role of blood lipids in the etiology of this malady, but Krista et al (1965) found that added dietary animal fat and cholesterol did not alter the incidence of aortic rupture.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In pigs and turkeys, defects in lysyl oxidase secondary to copper deficiency result in decreased and abnormal layering of elastin, resulting in subsequent arterial rupture. 3,4,11 The elastin within the vessels in cattle with Marfan syndrome is similarly abnormal, resulting in vascular rupture. 8 In humans with abdominal artery rupture, direct damage to the vessel wall or damage secondary to deposition of antigen-antibody complexes can result in fragmentation and break down of elastin.…”
Section: Discussionmentioning
confidence: 99%
“…DES implantations have been reported by Krista et al (1961Krista et al ( , 1965, Beall et al (1963), and to increase the incidence of aortic rupture in turkeys. Krista et al (1965) and reported a concomitant decrease in blood pressure with an increase in aortic rupture.…”
Section: Introduction T He Use Of Diethylstilbestrol (Des)mentioning
confidence: 90%